Tigridia potosina (Iridaceae; Tigridieae), a new species from the Sierra de Álvarez, San Luis Potosí, Mexico - López-Ferrari, Ana Rosa; Espejo Serna, Adolfo (Instituto de Ecología, A.C., 2002)
Tigridia potosina, a new species discovered in the Sierra de Álvarez, San Luis Potosí, Mexico, is described and illustrated. The new species belongs to subgenus Hydrotaenia and is morphologically similar to Tigridia multiflora (Herb.) Ravenna but is distinguished by the size and the color of tepals, and by the width of the floral cup. Also the new species may be confused, because of the flower color, with T. alpestris Molseed ssp. obtusa Molseed, but differs from that taxon in the form of tepals and in the larger style branches.